Peran Komunikasi Keluarga dalam Menciptakan Saling Pengertian dan Sarana Keharmonisan Keluarga pada Komunitas Tangan Di Atas (TDA) Perempuan Blitar - Meifilina, Andiwi; Sunandes, Aris; Magfiroh, Nurmaida (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Communication in the family should be understood and controlled by a mother or woman, the importance of a mother's role in a family makes the ability to educate through communication very important.Based on the explanation above, the author feels it is necessary to hold training on the role of family communication in creating a sense of mutual understanding and being a means of family harmony. Family communication training in creating a sense of mutual understanding and becoming a means of family harmony is carried out in service training carried out at the secretariat Blitar Women's Hands Up (TDA) community group, Pakunden Village, Blitar Cityon Friday, July 7 2024. The training participants consisted of 100 people who were women Blitar women's Hands Up (TDA) community group.There are several methods used in this training activity, including situation analysis, providing material, training, distributing questionnaires and evaluation. The objectives of this trial are: 1). To improve interpersonal communication skills, 2). To improve effective communication skills, 3) To improve verbal and non-verbal communication skills. The results of community service activities show that satisfaction with community service activities held by Blitar Islamic University is the result of the questionnaire, namelyability in family communicationBlitar women's Hands Up (TDA) communityplays a very important role in improving their self-quality, self-confidence and educational spirit. Service participants were satisfied with the community service activities held through training on the role of family communication with FISIPOL, Blitar Islamic University. This is proven by the results of the questionnaire, namely 62.4% and 37.6% agreed. Community service activities held through training on the role of family communication with Blitar Islamic University met the participants' expectations with the results of the questionnaire being 57.7% and 42.3% agreeing. Personnel/members of the community service activity team provide services according to participants' needs with the results of the questionnaire being 55.7% and 44.3% agreeing. Every complaint/question/problem raised was followed up well by the resource persons/members involved with the results of the questionnaire being 60.6% and 39.4% agreeing. If this activity is held again, I am willing to participate/involve with the results of the questionnaire being 51.5% and 48.5% agreeing.